The Plasticity and Developmental Potential of Termites - Revely, Lewis; Sumner, Seirian; Eggleton, Paul (Frontiers in Ecology and Evolution, 2021)
Phenotypic plasticity provides organisms with the potential to adapt to their environment and can drive evolutionary innovations. Developmental plasticity is environmentally induced variation in phenotypes during development that arise from a shared genomic background. Social insects are useful models for studying the mechanisms of developmental plasticity, due to the phenotypic diversity they display in the form of castes. However, the literature has been biased towards the study of developmental plasticity in the holometabolous social insects (i.e. bees, wasps and ants); the hemimetabolous social insects (i.e. the termites) have received less attention. Here, we review the phenotypic complexity and diversity of termites as models for studying developmental plasticity. We argue that the current terminology used to define plastic phenotypes in social insects does not capture the diversity and complexity of these hemimetabolous social insects. We suggest that terminology used to describe levels of cellular potency could be helpful in describing the many levels of phenotypic plasticity in termites. Accordingly, we propose a conceptual framework for categorising the changes in potential of individuals to express alternative phenotypes through the developmental life stages of termites. We compile from the literature an exemplar dataset on the phenotypic potencies expressed within and between species across the phylogeny of the termites and use this to illustrate how the potencies of different life stages of different species can be described using this framework. We highlight how this conceptual framework can help exploit the rich phenotypic diversity of termites to address fundamental questions about the evolution and mechanisms of developmental plasticity. This conceptual contribution is likely to have wider relevance to the study of other hemimetabolous insects, such as aphids and gall-forming thrips, and may even prove useful for some holometabolous social insects which have high caste polyphenism.